ANALISIS PROSPEK PENGEMBANGAN USAHATANI JERUK SIAM BERDASARKAN KELAYAKAN USAHA DI KECAMATAN SAMARANG KABUPATEN GARUT - Burhanudin; Kundrat (Program Studi Agroteknologi Faperta UNIBBA, 2021)
The prospect of siam oranges (Citrus nobilis var.Microcarva Hoslk) farming development in subdistrict of Samarang, the district of Garut. The objectives of this study is to evaluate : (1) basic of farmer’s consideration in developing their siam oranges farming business, (2) prospect of siam orange farming business development from the view points its investment feasibility aspects, and prospect of siam orange farming business development from the view points of its strength, weaknesess, opportunities and threat. A survey was conducted in this study with a sample consisted of 63 farmers respondent which sorted out through two stage cluster random sampling technique The result of this study indicated that : The Price of orange was mainly considered in developing siam orang in the subdistrict of Samarang. Siam Orange farming business in this subdistrict was profitable as indicated by its Net Present Value (NPV): Rp.209.975.657,81, Benefit cost ratio (B/C) ; 1,63 and Internal Rate of Return (IRR) : 28,83%. Payback periods was reached with the period of 5 years and 7 mounths after planting. Sensitivity analysis indicated that siam orange business still profitable, despite the increase in production costs and a 10% decrease in benefits to the assumption of delay years. SWOT analysis indicated that siam orange farming business in this subdistrict was on the Strength – Opportunity quadrant which mean that this business should be optimally encourged to enter the market.